Polemik Pengarusutamaan Kesetaraan Gender di Indonesia - Gusti Rahma Sari; Ecep Ismail (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
This research aims to discuss the implementation of gender equality in Indonesia. The research method is a qualitative type through literature study by applying content analysis. This research discusses the meaning, gender equality of Alquran perspective, and implementation in Indonesia. This research concludes that in the fields of education, law, family and government policies, gender equality gas been implemented. However, the issue of gender equality has not yet become mainstream so that it affecs the case of divorce in Indonesia. This research is only limited to the implementation of gender equality in Indonesia in several fields or sectors so that further research is needed in other fields. This research recommends the socialization of the concept of gender equality in the framework of Alquran to both men and women so that people get a complate understanding and create harmony.